Strong Reflexivity and Its Critics: Responses to Autoethnography in the German-Speaking Cultural and Social Sciences. (November 2016) - Ploder, Andrea; Stadlbauer, Johanna
This contribution explores autoethnography as a strongly reflexive approach to qualitative research and its reception in German-speaking sociology and cultural anthropology. Over recent years, our academic communities have developed an increased interest in autoethnography, although many reactions range from critical to hostile: It is accused of solipsism, narcissism, lack of arguments and theory, affective immediacy, non-criticizability, endorsement of neoliberal politics, a threat to disciplinary identity, and a strategic mistake in the fight for appreciation of qualitative research. We discuss each point of criticism and translate our insights into more general considerations on strong reflexivity in German-speaking cultural and social sciences.